NETest: serial liquid biopsies in gastroenteropancreatic NET surveillance - Mark J C van Treijen; Catharina M Korse; Wieke H Verbeek; Margot E T Tesselaar; Gerlof D Valk (Endocrine Connections, 2022)
Objective: Up to now, serial NETest measurements in individuals assessing the disease course of gastroenteropancreatic neuroendocrine tumors (GEPNETs) at long-term follow-up and treatment response were not studied. Design: The study was a longitudinal validation study of serial NETest measurements – a blood-based gene expression signature – in 132 patients with GEPNETs on therapy or watch-and-wait strategy. Methods: Serial samples were collected during 46 (range: 6–71) months of follow-up. NETest scores were compared with Response Evaluation Criteria in Solid Tumors version 1.1-defined treatment response (e.g. no evidence of disease (NED ), stable disease (SD) or progressive disease (PD)). Results: Consecutive NETest scores fluctuated substantially (range: 0–10 0) over time in individuals with SD (n = 28) and NED (n = 30). Follow-up samples were significantly higher in SD (samples 3–5) and NED subgroups (samples 2–5) compared with baseline results, without changes in imaging. In 82% of untreated patien ts with PD, consecutive NETest scores consistently remained high. In patients undergoing systemic treatment, the median pre-treatment NETest score in treatment-responders was 76.5 (n = 22) vs 33 (n = 12) in non-responders (P = 0.001). Patients with low pre-treatment scores had 21 months reduced progression-free survival (10 vs 31 months; P = 0.01). The accuracy of the NETest for treatment response prediction was 0.73 (P = 0.009). Conclusion: In patients not undergoing treatment, consecutive low NETest scores are associated with indolent behavior. Patients who develop PD exhibit elevated scores. Elevated results have important predictive value for treatment responsiveness and could be used for individualizing decisions on systemic therapy. The clinical value of follow-up NETest scores for patients who choose to watch and wait requires further study.